2014
DOI: 10.1016/j.jviromet.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Single genome amplification of proviral HIV-1 DNA from dried blood spot specimens collected during early infant screening programs in Lusaka, Zambia

Abstract: The ability to evaluate individual HIV-1 virions from the quasispecies of vertically infected infants was evaluated in a field setting at the Centre for Infectious Disease Research in Zambia. Infant heel-prick blood specimens were spotted onto dried blood spot (DBS) filter paper cards at government health clinics. Nucleic acid was extracted and used as a template for HIV-1 proviral DNA detection by a commercial Amplicor HIV-1 PCR test (Roche, version 1.5). On samples that tested positive by commercial diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…This observation is consistent with findings by others with DBS [9,17,19,21,23]. A possible and most advanced explanation of this repeated finding could be the contribution of intracellular HIV-1 DNA and RNA which is present in the DBS but not in the plasma counterpart [26,27]. Vidya et al [18] suggested that the contribution of intracellular HIV-1 DNA and RNA could be more relevant to specimens with low or undetectable levels viremia than to specimens containing higher levels of extracellular HIV-1 RNA.…”
Section: Discussionsupporting
confidence: 91%
“…This observation is consistent with findings by others with DBS [9,17,19,21,23]. A possible and most advanced explanation of this repeated finding could be the contribution of intracellular HIV-1 DNA and RNA which is present in the DBS but not in the plasma counterpart [26,27]. Vidya et al [18] suggested that the contribution of intracellular HIV-1 DNA and RNA could be more relevant to specimens with low or undetectable levels viremia than to specimens containing higher levels of extracellular HIV-1 RNA.…”
Section: Discussionsupporting
confidence: 91%
“…This observation is consistent with the findings reported by other research groups in terms of DBS [9, 17, 20, 22, 24]. The most advanced explanation of this repeated finding could be the contribution of intracellular HIV-1 DNA and RNA, which is present in the DBS but not in the plasma counterpart [27, 28]. Vidya et al .…”
Section: Discussionsupporting
confidence: 91%
“…At the completion of the cDNA synthesis, the remaining RNA was treated with RNaseOUT (Invitrogen Corp., Life Technologies), and the synthesis mixture was purified using a GeneJet DNA (Thermo Scientific Corporation, Waltham, MA) purification kit. A nested PCR reaction was performed on the cDNA eluate using Platinum Taq DNA polymerase (Invitrogen Corporation, Life Technologies) according to previously published amplification methods (Seu et al, ): a 1,200 bp sequence was first amplified using forward primer (CWF: 5′‐GAAGGACACCAAATGAAAGAYTG‐3′; HXB2 nucleotide position 2,044–2,066) and reverse primer (LSR1: 5′‐ACTGTTTTACATCATTAGTGTGGG ‐3′; HXB2 nucleotide position 3,651–3,628) and a second round PCR amplification using a forward primer (LSF1: 5′‐TCAGAGCAGACCAGAGCCAACAGCCCCA‐3′; HXB2 nt position 2,136–2,163) and reverse primer (Rev7: 5′‐ATCCCTGGGTAAATCTGACTTGCCCA‐3′; HXB2 position 3,370–3,345). Amplicons were directly analyzed via population‐based Sanger Sequencing using BigDye Terminator chemistry and protocols recommended by the manufacturer (Applied Biosystems, Foster City, CA), and sequencing reaction products were analyzed with an ABI 3130XL genetic analyzer (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%